KEPEMIMPINAN DALAM ADMINISTRASI PENDIDIKAN - Eti Robiatul Adawiah; Kun Nurachadijat (Program Studi Pendidikan Agama Islam, Universitas Majalengka, 2023)
Leadership in educational administration is very important to help achieve the desired educational goals. In the context of educational administration, leadership plays an important role in guiding and leading the people involved in the education system, including students, teachers, administrative staff, and parents. The purpose of writing this article is to determine the effectiveness of leadership in managing appropriate educational administration, so as to be able to manage human, financial and physical resources to support quality learning and teaching. Writing this article uses a qualitative method with a descriptive approach and data collection techniques in the form of literature studies. The research results show that overall, effective leadership in education administration can help create an inclusive, responsive, and effective education system in achieving the desired educational goals.